Quality in university teaching. An approximation from student’s perception - Montenegro Ordoñez, Juan (2020)
The objective was to build a notion of quality of university teaching, depending on the demand of the recipients of the service, the students, based on their opinions and perceptions, contrasting it with the notions that emerge or are considered in the respective regulations, given in the country. It was developed at the Universidad Señor de Sipán, Juan Mejía Baca Private University and Pedro Ruiz Gallo National University. The study design has been exploratory and descriptive, as well as hermeneutical phenomenological type and cross-sectional. The sample consisted of 164 students. 90% agree that a quality university must necessarily have quality teachers, and indicates that this quality teacher must demonstrate mastery in four dimensions: thematic dimension, methodological dimension, scientific dimension, and ethical dimensión, according to the literature consulted.